The Tourism Potential of Post-mining Heritage Sites: The Cyprus Mining Cooperation in Lefka, Cyprus - Vehbi, Beser Oktay; Misirlisoy, Damla; Gunce, Kagan; Yuceer, Hulya (Springer Heidelberg, 2022)
The mining sites have geo-scientific, industrial, cultural, aesthetic, economic, historic and anthropological potentials for the development of tourism. Lefka with an ancient history of mining and having rich geodiversity as well as various historical and cultural monuments, archaeological sites along with poor economic conditions can develop tourism with mining tourism goals. The study aims to examine the tourism potential of post-mining heritage sites as part of a strategic approach and tool for planning that encourages local development through the case of the Cyprus Mining Cooperation (CMC), a derelict copper mining field in Lefka, North Cyprus. Established during the British administration of the island, CMC covers a large area that comprises of mine fields, processing units, laboratories, workers houses and other related public buildings serving the whole complex, which were left derelict about sixty years ago. The study presents the values-scientific, aesthetic, economic, historical and cultural-associated with the site and its components, the criteria for their conservation and reuse opportunities for tourism purposes. Conservation strategies are suggested within the framework of 'mining tourism' to present the heritage significance of the site.
Keywords: Mining heritage; Mining tourism; Geoheritage; Cyprus Mining Cooperation; Lefka; Cyprus